Direct interspecies electron transfer via conductive materials: A perspective for anaerobic digestion applications. (April 2018) - Park, Jeong-Hoon; Kang, Hyun-Jin; Park, Kang-Hee; Park, Hee-Deung
Graphical abstract: Highlights: DIET via conductive materials is a promising technology for anaerobic digestion. Critical reviews on current understanding of DIET were conducted. Relevant studies published to date were systematically analyzed. Future perspectives for practical applications are proposed. Abstract: Anaerobic digestion (AD) is a microbial process that produces renewable energy in the form of methane by treating organic waste and high-strength wastewater. Recent studies have demonstrated that conductive materials can promote direct interspecies electron transfer (DIET) between exoelectrogenic bacteria and methanogenic archaea. DIET via conductive materials is more effective for methane production than interspecies electron transfer using electron carriers such as hydrogen, a principal route of methane production in conventional AD. This critical review presents the current understanding of DIET via conductive materials for methane production, summarizes the relevant studies published to date, and analyzes these studies with regard to conductive materials, substrates, inocula, performance, and microorganisms. Based on this analysis, possible future directions are suggested for practical DIET applications via conductive materials in AD.